Antioxidant Properties of Biodiesel-Diesel Blends and Non-Isothermal Kinetic Studies of Schiff-Based Isatin-Thiosemicarbazone Derivatives - Karakullukcu, Nalan Turkoz; Muglu, Halit; Yakan, Hasan; Yilmaz, Volkan Murat; Ince, İkbal Agah (MDPI AG, 2024)
Biodiesel has several drawbacks, such as being prone to oxidation, having reduced stability, and having limited storage time. Antioxidants compatible with biodiesel are being used to address its drawbacks. The use of antioxidants in biodiesel has a significant impact on the environment and economy, especially in promoting sustainable energy. The study used blends consisting of 20% biodiesel and 80% diesel fuel. Isatin-thiosemicarbazones were tested as additives in blends at a concentration of 3000 parts per million (ppm) using an oxifast device. Comparing them to the chemical antioxidant Trolox. FT-IR, DSC, and TGA were used to characterize these samples. DSC measured sample crystallization temperatures (Tc). Samples with antioxidants showed decreased values compared to the non-antioxidant diesel sample D100. Several DSC tests were conducted to determine the antioxidant strengths of various samples. The results showed that the FT-IR spectrum's antioxidant effect regions grow clearer with antioxidants. The extra antioxidant is effective. Biodiesel's oxidative stability improves with isatin-thiosemicarbazones at varying concentrations. The kinetics of thermal decomposition of isatin-thiosemicarbazones under non-isothermal conditions have been determined using the Kissinger, Ozawa, and Boswell techniques. The activation energies of compounds 1 and 2 were calculated 137–147 kJ mol-1 and 173–183 kJ mol-1, respectively.
Keywords: 13. Climate action; 7. Clean energy